Life-style and occupational risk factors for early onset dementia in an Italian community. (30th September 2020) - Adani, G; Filippini, T; Garuti, C; Malavolti, M; Vinceti, G; Zamboni, G; Tondelli, M; Vinceti, M; Chiari, A
Abstract: Background: Early onset dementia (EOD) is defined as dementia with symptoms onset before 65 years, deeply impacting on patients' employment and income, as well as on their families. Little is known about role of occupational and life-style risk factors, we aimed at assessing their role in disease etiology. Methods: Using a case-control study design, we recruited all EOD cases resident in Modena province from October, 2016 to October, 2019, and a referent population drawn from patients' care-givers. We investigated residential, life-style history, and occupational and environmental exposures to toxics through a self-administered questionnaire. We used a multivariate unconditional logistic regression model adjusted for sex, age, and education to calculate odds ratios (ORs) and 95% confidence intervals (CIs) of EOD risk for exposed vs. non-exposed subjects. Results: Overall, fifty-eight EOD cases and fifty-four controls agreed to participate. Possible life-style risk factors are to be widowed (10.3% of cases vs. 2% of controls), and to have a lower educational attainment. Also smoking (OR 1.3, 95% CI 0.6-2.9), playing football (OR 2.2, 95% CI 0.5-9.3) or cycling (OR 2.3, 95% CI 0.4-13.4) were associated with higher EOD risk, although overall sport practice appeared to be a powerful protective factor (OR 0.4, 95% CI 0.2-0.9), particularly swimming (OR 0.2, 95% CI 0.0-0.8). Among occupational factors, disease risk was associated with exposure to aluminum (OR 2.6, 95% CI 0.4-15.7), pesticides (OR 2.3, 95% CI 0.7-7.8), and dyes, paints or thinners (OR 1.7, 95% CI 0.6-5.0). Finally, disease risk was not associate to overall history of any trauma, while head trauma and especially upper arm trauma showed positive association. Conclusions: Despite the study limitations, our results appear to support a role of modifiable risk factors in EOD etiology, particularly of some chemical exposures and professional sports, while overall sports practice may have a beneficial effect. Key messages: Some modifiable environmental, occupational and life-style risk factors seem associated with EOD onset. Awareness of EOD environmental and occupational risk factors, as well as life-style ones, is advisable on a public health perspective.